Marriage Actualization of the Malay Indigenous Peoples of Riau Province in the Legal Perspective - Ratna Riyanti; Yuli Heriyanti; Hafiz Sutrisno (Budapest International Research and Critics University, 2022)
This research concerns the analysis and studies related to the normative legal postulates contained in the provisions of Article 18B paragraph (2) and Article 281 paragraph (3) of the 1945 Constitution after the Amendment, which is supported by sectoral laws related to the protection and recognition of the legal community custom. In this case, the problem written is about how the constitutionality position of the existence of customary law and customary law community alliances is. It aims to answer academic questions about the protection of the traditional rights of the Sakai Tribe legal community. The research method used is sociological juridical law research, namely; research that departs from positive legal norms and doctrines enriched with data and facts from the field. The research results are; that legally in the 1945 Constitution with sectoral laws against customary law communities, in general it has been protected. However, the implementation of policies from both the central and local governments has not been able to protect the traditional rights of the indigenous people of the Sakai Tribe. Although the area is the source of life for the Sakai people, it is rich in natural resources that are economically valuable. The absence of a Customary Regional Regulation proves that the Riau provincial government favors the Sakai Tribe customary law community. This research is descriptive analytical, namely research that will describe, examine and explain thoroughly about problems and the legal system and examine them systematically so that they can be more easily understood and concluded.